Kajian Numerik Tata Letak ventilator Ruang Kamar Mesin Di Kapal Coaster 2000 GT - Prasetyo Nugroho Agung; Muhadi Eko Prayitno Muhammad; Gafur Abdul (Politeknik Perkapalan Negeri Surabaya, 2018)
HVAC (Heat Ventilation & Air Conditioning) is it most important for the vessel. Engine room is very important part from the vessel. Because there are have main engine as engine driven and auxiliary engine as complement for the systems. From Biro Klasifikasi Indonesia rules said : if must be 45 â°C for every vesselâ€™s ventilation at engine room. Design at engine room must be know how efficients of ductingâ€™s design and how about heat distribution of every part at engine room, and this design can help for air change from exhaust air and keep air distribution to be constant. From this experients we are know if the temperature at ME Room is 47 â°C (exceed from BKIâ€™s standart) and 36 â°C at AE Room. So, we need to redesign for this condition. From the result we are know if recondition at ME Room change to be 39 â°C. ventilation air position and ducting track design very important to get velocity air distribution who intake in engine room and keep the temperature to be constant (not exceed 45 â°C).